"Leaderless" resistance? An anatomy of female leadership in Orang Asli grassroots movements - binti Padzil, Ruhana; Somiah, Vilashini (Wacana, Journal of the Humanities of Indonesia, 2023)
This article unpacks community-level female leadership among Malaysia’s indigenous Orang Asli community. The power dynamics of this community’s relationship with state institutions have been uneven. Critics accuse the authorities of infantilizing the community, through gendered and patriarchal behaviour (for example, male government officers only interact with male heads of communities). Based on the fieldwork including seven interviews with female and male Orang Asli grassroots leaders of an independent, pro-indigenous movement – one which is apparently “leaderless” in terms of its organizational structure – we show how they challenge the abovementioned attitudes through neo-empowerment and agentic efforts, through collective narratives of the environment, camaraderie and compassion. These grassroots efforts also appeal to a new cohort of indigenous people, embody gentle negotiation strategies, and recognize gendered discourses of agency and control. We show how this leads to the creation of a more inclusive, progressive, and feminist-driven empowerment strategy, eventually building resistance to traditional patriarchal structures.